Dari Luka Menuju Penerimaan: Kisah Remaja Perempuan Korban Familial Sexual Abuse - Venessya Manuhutu; Sri Aryanti Kristianingsih; Enjang Wahyuningrum (Kuras Institute, 2026)
Adolescents are a vulnerable group to sexual violence due to a lack of sexual education, media influence, and complex social dynamics that exacerbate their vulnerability to sexual violence. This vulnerability is reflected in data on sexual violence in Indonesia, with 16,781 cases of sexual violence in 2024. Sexual violence is not only perpetrated by strangers but can also be perpetrated by parents or family members. This study aims to describe and understand the process of self-acceptance in adolescent girls who are victims of familial sexual abuse. Data were collected through observation and in-depth interviews with two participants who experienced familial sexual abuse at the ages of 14 and 13. The results showed that the participants had self-acceptance, reflected in the awareness that they still have support, a greater appreciation for life, and the choice to continue living. The process of self-acceptance can occur in stages, namely through resisting, exploring, tolerating, allowing, and befriending. This process is shaped by internal and external factors that have the potential to increase self-acceptance.